Analisis Gaya Bahasa, Psikologi dan Nilai-Nilai Pendidikan dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar - Agus Darmuki (Jurnal Penelitian Pendidikan, 2014)
This research aims at revealing a clear depiction of figurative language, literature psychology and educational values of Novel Small Letters to God, Davonar Agnes’ work. It is kind of descriptive qualitative research method. And the source of data is by using Novel Small Letters to God, of Davonar Agnes’ work. The data which is used is the result of the researched annotation in the form of sentences containing figurative language and educational values of Novel Small Letters to God. Furthermore, the data collection was carried out by using literature technique or document. The analysis activity is begun from data reduction that allows the researcher to discharge and enter the useful data as well as triangulation which allows researcher to acquire the validity of the data. Thus, the reduced data as well as triangulation will provide a clear depiction and facilitate researchers for collecting the further data. Based on the research findings, it can be concluded that Novel Small Letters To God has psychology, figurative language and educational values. Novel Small Letters To God, of Agnes Davonar’s work is found to have id, ego and super-ego. This novel uses figurative language as follows: hyperbole, personification, climax, irony, antithesis, satire, litotes, anastrophe, paronomasia, periphrasis, paralipsis, apostrophe, and contains the educational values, including religious, moral, and social value.